A new conceptual framework for maternal morbidity. (23rd May 2018) - Filippi, Veronique; Chou, Doris; Barreix, Maria; Say, Lale; ,
Abstract: Background: Globally, there is greater awareness of the plight of women who have complications associated with pregnancy or childbirth and who may continue to experience long‐term problems. In addition, the health of women and their ability to perform economic and social functions are central to the Sustainable Development Goals. Methods: In 2012, WHO began an initiative to standardize the definition, conceptualization, and assessment of maternal morbidity. The culmination of this work was a conceptual framework: the Maternal Morbidity Measurement (MMM) Framework. Results: The framework underscores the broad ramifications of maternal morbidity and highlights what types of measurement are needed to capture what matters to women, service providers, and policy makers. Using examples from the literature, we explain the framework's principles and its most important elements. Conclusions: We express the need for comprehensive research and detailed longitudinal studies of women from early pregnancy to the extended postpartum period to understand how health and symptoms and signs of ill health change. With respect to interventions, there may be gaps in healthcare provision for women with chronic conditions and who are about to conceive. Women also require continuity of care at the primary care level beyond the customary 6 weeks postpartum. Abstract : A new Maternal Morbidity Measurement framework is presented, highlighting the consequences of maternal morbidity and the measurement required to capture the needs of women, providers, and policy makers.